An unusual cause of lower gastrointestinal haemorrhage. (13th December 2011) - Janmohamed, Azara; Noronha, Lizanne; Saini, Ashish; Elton, Colin
Abstract : A previously unreported cause of lower gastrointestinal haemorrhage in a 63-year-old female patient on clopidogrel for cardiac comorbidities is presented. Endoscopy suggested a small bowel or colonic aetiology but failed to accurately localise the source. The patient became haemodynamically unstable despite conservative management and temporary cessation of clopidogrel. CT angiography demonstrated a pseudoaneurysm arising from the superior rectal artery. Percutaneous embolisation using coils was performed to successfully occlude the pseudoaneurysm, prevent further haemorrhage and avoid emergency colonic resection.